Taxon sampling and alternative hypotheses of relationships in the euphyllophyte plexus that gave rise to seed plants: insights from an Early Devonian radiatopsid. Issue 2 (22nd June 2021) - Toledo, Selin; Bippus, Alexander C.; Atkinson, Brian A.; Bronson, Allison W.; Tomescu, Alexandru M. F.
Summary: An abrupt transition in the fossil record separates Early Devonian euphyllophytes with a simple structure from a broad diversity of structurally complex Middle–Late Devonian plants. Morphological evolution and phylogeny across this transition are poorly understood due to incomplete sampling of the fossil record. We document a new Early Devonian radiatopsid and integrate it in analyses addressing euphyllophyte relationships. Anatomically preserved Emsian fossils (402–394 Ma) from the Battery Point Formation (Gaspé, Quebec, Canada) are studied in serial sections. The phylogenetic analysis is based on a matrix of 31 taxa and 50 characters emphasising vegetative morphology (41 discrete, nine continuous). The new plant, Kenrickia bivena gen. et sp. nov., is one of very few structurally complex euphyllophytes documented in the Early Devonian. Inclusion of Kenrickia overturns previously established phylogenetic relationships among Radiatopses, reiterating the need for increased density of Early Devonian taxon sampling. Kenrickia is recovered as the sister lineage to all other radiatopsids, a clade in which paraphyletic Stenokoleales led to a lignophyte clade where archaeopterids and seed plants fall into sister clades. Our results shed light on early euphyllophyte relationships and evolution, indicating early exploration of structural complexity by multiple lineages and reiterating the potential of a single origin of secondary growth in euphyllophytes.